Assessment of gender distribution in dengue surveillance data, the Lao People's Democratic Republic - Bouaphanh Khamphaphongphane; Panom Phongmanay; Tamano Matsui; Reiko Tsuyuoka; Hannah C Lewis; Sara Stone; Manilay Phengxay; Onechanh Keosavanh; Nouda Prasith; Yuzo Arima (World Health Organization Regional Office for the Western Pacific, 2013)
Objective: Adolescent and young adult males account for a large proportion of dengue cases reported through national surveillance systems in the Western Pacific Region. To preliminarily assess the validity of these observed distributions, a field investigation was conducted in the Lao People's Democratic Republic's Savannakhet Province in November 2011. Methods: Mixed quantitative and qualitative methods were used. Dengue surveillance data from Savannakhet Province, and aggregate hospital admission data from the Savannakhet Provincial Hospital for outpatients and inpatients were analysed by age and sex. Unstructured informal interviews were conducted with local health care workers, primary and secondary school officials and villagers. Results: An excess of males was found among reported dengue cases in Savannakhet Province in the 15-49 year age group. Females in the same age group, however, were found to access health care more than their male counterparts. Qualitative assessments attributed this distribution to young females being more health-conscious and having greater health care-seeking behaviour. Discussion: The excess of male dengue cases in the surveillance data appeared to be associated with a truly higher risk of dengue rather than greater health care access or health care-seeking behaviour by young men. This investigation indicated the importance of assessing the reported surveillance data within the context of health care utilization behaviour of the population under surveillance.